Analisis Penerimaan Produk Domestik Regional Bruto Sektor Pariwisata di Kabupaten badung - Marta, Nani; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 7, Juli 2014 (pp.282-336), 2014)
The purpose of this study was to determine the effect of simultaneous and partially between the number of foreign tourists, the U.S. dollar exchange rate, and the level of security on the acceptance of regional gross domestic product in Badung tourism sector. Source of data used are secondary data sources. The analysis technique used is multiple regression analysis with the observation period from year 1998 to 2012. F test results indicate that the number of foreign tourists, the U.S. dollar exchange rate, and simultaneously affect the security level of the regional gross domestic product acceptance in Badung tourism sector. T test results showed that the number of foreign tourists and the U.S. dollar exchange rate has a positive effect, while the security level had no effect on gross regional domestic product acceptance in Badung tourism sector.
Keywords: regional gross domestic product; the number of foreign tourists; the U.S. dollar exchange rate; the level of security